PENERAPAN KEKANGAN MULTI TITIK DALAM ANALISA STRUKTUR - Mallisa, Zet (MEKTEK, 2007)
The paper presents the use of an algorithm to apply constraint to a governing system of simultaneous equations. The method consists of the implementation of the constraints directly on the system of simuitcineous gouerning equations prior to the solution operations. By the application of the method, problematic aspects such as possibility of the enlargement of the coefficient matrix size, or possible â€œill-conditionâ€ of the matrix, can he avoided.As a by-product, the met hod can also be used as a tool to compute for support reactions. The method can he applied suitably well in a computer analysis program.